Analisis Profitabilitas Perkebunan Dalam Industri Pengolahan Gula Merah - Adam, Ramli; Nugroho, Gatot Wahyu; Noor, Iqbal (PT Alahyan Publisher Sukabumi, 2025)
This study aims to analyze the profitability of plantation businesses in the brown sugar processing industry in Kampung Cikangkung, Citanglar Village, Surade District, Sukabumi Regency. This research employs a descriptive qualitative method with a case study approach. Data were collected through observation, in-depth interviews, and documentation involving the business owner, plantation supervisor, and production workers. The data analysis focuses on identifying the production process, cost structure, revenue, and profitability indicators, including Gross Profit Margin (GPM), Operating Profit Margin (OPM), and Return on Investment (ROI). The results indicate that the brown sugar production process is still conducted using traditional methods, starting from sap tapping, boiling, molding, to packaging. The cost structure is dominated by variable costs, particularly labor wages and fuel expenses. The average monthly revenue of the business is Rp 52,000,000 with total production costs of Rp 38,220,000, resulting in a net profit of Rp 13,780,000 per month. The profitability analysis shows a GPM and OPM of 26.5% and an ROI of 9.18% per month, indicating that the brown sugar processing business is financially profitable and feasible. The factors influencing profitability include technical, economic, managerial, as well as social and environmental factors, including the implementation of a land management system based on grants/zakat.This study is expected to provide useful insights for improving efficiency, financial management, and sustainability in the development of brown sugar agroindustry.